Increase in Labour Productivity in the Context of FDI Inflows into the Automotive Industry of Visegrad Group Member States - Dudáš, Tomáš, 1976-
Rast produktivity práce v kontexte s prílevom PZI do automobilového priemyslu krajín V4.